ANALYSIS OF THE SECURITY PROBLEMS OF FIFTH GENERATION MOBILE NETWORKS - Imanbayev А.Ж.; Tynymbayev С.; Odarchenko Р.С.; Alikhankyzy Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
For now, the development of 5G mobile networks will have a significant impact on security. The 3GPP 5G standard is independent in the sense that it is flexible enough to allow for different types of physical and virtual overlap between the radio access network and the core of the network. The separation of functions between the radio access network and the core raises questions about competitiveness and performance. This article first looks at the security requirements of 5G, including security requirements for business applications, network architecture, air interface, and user privacy. On this basis, the challenges faced by the current mobile security architecture are analyzed and internal security elements are examined from a network architecture perspective. Subsequently, taking into account the security resources and technical characteristics brought by innovations in 5G network and radio interface technologies, the current state of research and development trends of the main technologies for additional 5G security support, including physical layer security, encryption and the use of blockchain technology in 5G, are presented, as well as some countermeasures and proposals to protect 5G networks.